2022
DOI: 10.4314/bcse.v36i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of essential oils from various parts of Gladiolus candidus, Ranunculus multifidus, Artemisia abyssinica and Crinum abyscinicum

Abstract: ABSTRACT. The essential oil compositions of Gladiolus candidus, Ranunculus multifidus, Artemisia abyssinica and Crinum abyscinicum were analyzed with gas chromatography-mass spectrometry (GC-MS). The principal components in the leaves, stems and rhizomes of G. candidus were eudesmol, 1-naphthalenepropanol and oleic acid, respectively. α-Terpineol, alloocimene  and p-menth-2-en-1-ol from leaves, bulbs and roots were respectively the major constituents of C. abyscinicum. The aerial part of R. multifidus furnishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…According to the literature, no studies on the identification of C. mildbraedii bark essential oil components have been published. The components of the essential oil were identified by comparing their MS patterns and retention index (RI) with those of known chemicals published in the literature [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The chemical composition of the essential oil of C. mildbraedii bark was quantified using GC-FID and identified via GC-MS. Table 5 shows 30 compounds identified, representing 65% of all compounds detected in the GC-MS investigation of the essential oil, with 9 sesquiterpene hydrocarbons (26%), 7 oxygenated sesquiterpenes (22%) and 14 other compounds (17%).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, no studies on the identification of C. mildbraedii bark essential oil components have been published. The components of the essential oil were identified by comparing their MS patterns and retention index (RI) with those of known chemicals published in the literature [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The chemical composition of the essential oil of C. mildbraedii bark was quantified using GC-FID and identified via GC-MS. Table 5 shows 30 compounds identified, representing 65% of all compounds detected in the GC-MS investigation of the essential oil, with 9 sesquiterpene hydrocarbons (26%), 7 oxygenated sesquiterpenes (22%) and 14 other compounds (17%).…”
Section: Resultsmentioning
confidence: 99%
“…176,177 Of the medicinal plants employed to treat human health problems, Justicia schimperiana, Embelia schimperi, Olinia rochetiana and Euclea schimperi which were used to treat liver disorders, tapeworm infection, general gastrointestinal complaints, and skin diseases, respectively, scored the highest FL and ROP values, which are measures of therapeutic potential. 35 Justicia schimperiana was reported to have shown antioxidant, 178 lousicidal and acaricidal, 179 anticancer 180 and antimalarial 181 activities. Crude extracts of Embelia schimperi exhibited anthelmintic 182 and antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“… 57 Likewise, another study performed in Adama, Ethiopia, reported that the aerial part of R. multifidus displayed impressive activity against S. aureus and S. pyogenes . 58 …”
Section: Discussionmentioning
confidence: 99%
“…57 Likewise, another study performed in Adama, Ethiopia, reported that the aerial part of R. multifidus displayed impressive activity against S. aureus and S. pyogenes. 58 Based upon the results of antibacterial activities, only two plants, such as C. asiatica and S. marianum, were selected for further advanced assays, such as the mechanism of antibiosis and cytotoxicity. Our findings revealed some differences in the MIC and MBC values corresponding to the ATCC and MDR isolates of bacteria tested.…”
Section: Dovepressmentioning
confidence: 99%